2015
DOI: 10.1186/s12989-015-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral absorption of PEG-coated versus uncoated gold nanospheres: does agglomeration matter?

Abstract: BackgroundParticle size is thought to be a critical factor affecting the bioavailability of nanoparticles following oral exposure. Nearly all studies of nanoparticle bioavailability focus on characterization of the primary particle size of the material as supplied or as dosed, and not on agglomeration behavior within the gastrointestinal tract, which is presumably most relevant for absorption.MethodsIn the study reported here, snapshots of agglomeration behavior of gold nanospheres were evaluated in vivo throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…If biliary excretion of a nanoparticle is substantial, this can result in an underestimation of oral bioavailability from urinary and fecal measurements. Also, there is evidence that ingested nanoparticles can become trapped within the gastrointestinal tract, neither absorbed systemically nor excreted in feces for a month or more after an oral dose (Hinkley et al, 2015). This too can lead to errors in bioavailability assessment from fecal measurements, at least in theory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If biliary excretion of a nanoparticle is substantial, this can result in an underestimation of oral bioavailability from urinary and fecal measurements. Also, there is evidence that ingested nanoparticles can become trapped within the gastrointestinal tract, neither absorbed systemically nor excreted in feces for a month or more after an oral dose (Hinkley et al, 2015). This too can lead to errors in bioavailability assessment from fecal measurements, at least in theory.…”
Section: Discussionmentioning
confidence: 99%
“…PEG coating can also be important in reducing agglomeration of ingested AuNPs within the GI tract. Native (uncoated) AuNPs were found to agglomerate rapidly and extensively when given orally to mice, while PEG-coated AuNPs remained dispersed as primary particles throughout GI transit (Hinkley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in superior animal models reported scarce or no translocation of gold nanoparticles after oral administration depending on the dosing regime, NP size and surface properties but without a clear trend. [66,67] Therefore, we believe NP size can also have an influence in C. elegans, together with the exposure concentration and the presence/absence of recovery time.…”
Section: Interaction With the External And Pharyngeal Cuticlementioning
confidence: 99%